MODEL ORIENTASI KEWIRAUSAHAAN DALAM PENINGKATAN KINERJA BISNIS UKM BERBASIS KUALITAS IMPLEMENTASI STRATEGI DAN KETANGKASAN INOVASI (Studi pada UKM Industri Konveksi dan Bordir di Kabupaten Kudus) - Yopireno Satrya Pramuditya; Mahfudz Mahfudz (Jurnal Akuntansi dan Pajak, 2023)
This study aims to develop a new conceptual model based on the mediating role of various variables that fills the research gap between entrepreneurial orientation and business performance. able to make a contribution to the development of strategic management science in the proportion of management science. The independent variable is Entrepreneurship Orientation, the dependent variable is Business Performance, and the intervening variable is innovation agility and strategy implementation quality. The data used in this study are primary data derived from the distribution of research questionnaires.The population in this study are UKM, small and medium business in Kudus Regency, especially those engaged in the convection and embroidery industrial sector with a total of 196 convection and embroidery UKM industries in Padurenan District. The sample of this research is limited to 110 UKM of the convection and embroidery UKM industry in Kudus Regency. This research uses Structural Equation Modelling (SEM) analysis technique with AMOS 24.0 analysis tool.The findings show that the Entrepreneurial Orientation has a significant positive effect on Innovation Agility, the Entrepreneurial Orientation has a significant positive effect on the Quality of Strategy Implementation, Innovation Agility has a significant positive effect on the Quality of Strategy Implementation, the Quality of Strategy Implementation has a significant positive effect on Business Performance, and Innovation Agility has a significant positive effect on Business Performance. This study shows that companies must establish an entrepreneurial orientation, Innovation Agility, and improve the quality of strategy implementation so that they can improve business performance both directly. Keywords: Entrepreneurship Orientation, Innovation Agility, Implementation Quality, and MSME Business Performance